Probiotics as a Novel Approach in the Treatment of Psoriasis – A Literature Review - Chajnowska, Aleksandra; Stępień, Julia; Zach, Małgorzata; Suchcicka, Wiktoria; Borowy, Aleksandra; Guzowska, Julia; Sobczyk, Maciej; Wołoszyn, Barbara; Rzeźnik, Patrycja; Stachera, Weronika (Journal of Education, Health and Sport, 2025)
Psoriasis is a chronic, immune-mediated inflammatory skin disease. Recent studies have demonstrated a decreased diversity in the gut microbiota of individuals with psoriasis, suggesting a potential correlation between intestinal dysbiosis and disease severity. Emerging evidence highlights the relevance of the gut–skin axis, where shifts in microbial composition—marked by increases in certain bacterial species and reductions in others—may contribute to systemic inflammation. These microbial imbalances have been associated with immune dysregulation, including activation of inflammatory pathways involving T helper 17 (Th17) cells, which play a pivotal role in psoriasis pathogenesis. As a result, increasing attention is being directed toward modulating the gut microbiome as a therapeutic strategy. This review aims to evaluate the efficacy of probiotics as an adjunctive treatment in patients with psoriasis. The analysis of current literature indicates that probiotic supplementation, particularly with strains from the Lactobacillus and Bifidobacterium genera, may improve clinical outcomes when used alongside conventional therapies. Most of the reviewed studies reported statistically significant improvements in comparison to control groups. Nevertheless, large-scale, long-term clinical trials are required to fully elucidate the role of gut microbiota modulation in the management of inflammatory skin disorders.